Sosialisasi Manajemen Alat Mesin Pertanian Dalam Upaya Optimalisasi Produksi Padi Sawah Petani Desa Mata Air - Romi Fahri; Iis Janisa; Tolyaret Penuam; Abraham Ismail Pulungan; Tuti Wardani Siregar (PATRIOTIKA: Jurnal Inovasi dan Pemberdayaan Masyarakat, 2026)
The irrigated rice farming sector in Indonesia faces challenges of labour shortages and soaring production costs, which necessitate modernisation through mechanisation. However, the implementation of agricultural machinery and equipment is often hampered by low technological literacy and a lack of understanding of maintenance management at the farmer level. This community service activity aims to bridge the technical knowledge gap through outreach and education on strategies for the effective and efficient use of agricultural machinery. The method employed is a participatory approach involving lecturers as expert resource persons and students as field facilitators through four stages: problem identification, thematic education, field practice demonstrations, and evaluation. The results of the activity indicate that the transfer of knowledge regarding the three main pillars of mechanisation—appropriate effectiveness, operational efficiency, and maximisation of function—successfully shifted farmers’ mindset towards becoming professional technology managers. The application of appropriate operational patterns has been proven to reduce production costs by 25–30%.